Proces wyłonienia się kanonu biblijnego w świetle rękopisów z Qumran - Klukowski, Michał (Łódzkie Studia Teologiczne, 2022)
The article deals with the emergence of the biblical canon in the light of the Qumran manuscripts. In the first part of the article, the author explains the terminology of the literature on the subject. In the second part, it presents the criteria on the basis of which a given book is considered authoritative. In the third part, it presents the issues of data interpretation based on these criteria.